Physical activity is more related to adiposity in hypertensive than nonhypertensive middle-aged and older adults - Tebar, William R. [UNESP]; Ritti-Dias, Raphael M.; Saraiva, Bruna T.C. [UNESP]; Scarabottolo, Catarina C. [UNESP]; Canhin, Daniel S. [UNESP]; Damato, Tatiana M.M. [UNESP]; Aguilar, Beatriz A.S. [UNESP]; Christofaro, Diego G.D. [UNESP] (Wolters Kluwer, 2020)
Objective Adiposity is the main risk factor for hypertension and is negatively related to physical activity. However, it is not clear if this relationship is different according to hypertension. The present study aimed to analyze the relationship of physical activity in different domains with adiposity in hypertensive and nonhypertensive adults. Participants and methods A sample of 843 adults (61.6% of female) was randomly selected, with a mean age of 56.6 (±18.3) years. Diagnosed hypertension and the use of medicines were self-reported. Physical activity was assessed by questionnaire and blood pressure was measured by the oscillometric device. Adiposity indicators were as follows: BMI, waist circumference, and waist-to-height ratio (WHtR). Results Hypertension was reported by 44.7% of sample, being higher among older-aged, obese, elevated waist circumference and WHtR, and low physical activity groups. Physical activity was negatively related to BMI (leisure-time physical activity β = -0.070, total physical activity β = -0.082), waist circumference (leisure-time physical activity β = -0.031, total physical activity β = -0.037), and WHtR (leisure-time physical activity β = -4.917, total physical activity β = -5.996) in hypertensive adults. Hypertensive adults who had obesity were more likely to be less active at leisure physical activity [odds ratio (OR) = 2.25] and in total physical activity (OR = 2.46) than hypertensive adults with normal weight. Hypertensive adults with elevated waist circumference and elevated WHtR were more likely to be less active in total physical activity than those hypertensive adults with normal values (OR = 2.34 and 3.33, respectively). Conclusion Leisure time and total physical activity were related to adiposity only in hypertensive adults. Higher physical activity levels could be important to adiposity control in hypertensive population.
Keywords: central fat; hypertension; leisure time; obesity; physical activity